Science with a smile : (Institute of Physics Publishing, 1992)
This anthology presents the reader with a fascinating view of the whimsical side of science. A unique and historical collection of humorous stories, anecdotes, verse and cartoons touching every science has been meticulously compiled by the author from worldwide sources.